THE ROLES OF ICT IN CULTIVATING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS - Teguh Sulistyo; Octavia Widiastuti; Agus Soleh (JURNAL SOSIAL HUMANIORA (JSH), 2018)
The use of Information and Communication Technology (ICT) in all levels of education has been implemented broadly for years. This paper aims at reporting the power of ICT in cultivating elementary school students’ character. The recent study, basically, is twofold: First, to find out how elementary school students behave towards the use of ICT in thr form of short videos and Hot Potatoes in the classrooms; second, to investigate the positive character of the students during the implementation of ICT. There were 45 fifth graders of an elementary school  joining the project. They were treated using ICT in the classroom, and they were encouraged to express their opinion dealing with the use of ICT in the classroom. The findings of the present study suggest that teachers should facilitate their students with ICT for it is necessary to build positive student character, and it motivates them to behave well during the class